Comparison of Short-term Outcomes of Percutaneous Coronary Intervention between Young Male and Female Patients with Acute Coronary Syndrome - Cader, Fathima Aaysha; Rahman, Afzalur; Rahman, Mohammad Arifur; Zaman, Shahana; Arefin, Md Minhaj; Reza, Abeeda Tasnim; Matin, Mohammad Abdul; Islam, Md Shariful; Afroz, Fahdia; Md Jafor, Abul Hasnat (Bangladesh Heart Journal, 2018)
Background:Young women undergoing percutaneous coronary intervention (PCI) for acute coronary syndrome (ACS) experience greater short-term adverse events than young men. There is a scarcity of data on the short-term adverse outcomes between young Bangladeshi males and females with ACS undergoing PCI.Objectives: This study was conducted to compare the short-term outcomes of PCI between young males and females presenting with ACS. Methods: This prospective observational study was done in the Department of Cardiology, National Institute of Cardiovascular Diseases (NICVD) fromApril 2016 to March 2017. 190 young patients with ACS and undergoing PCI were enrolled. They were equally divided into two groups, group I (young females <55 years) and group II (young males <45 years). Results: The mean age of young females and males was 43.8±6.9 years and 40.1±4.3 years respectively. Young women had significantly higher risk factors of hypertension (62.1% vs 33.7%, p<0.0010) and diabetes (57.9% vs 31.6%, p<0.001) in comparison to young men. Overall, young women experienced significantly greater incidence of short-term adverse events in comparison to young men (14.7% vs. 6.3%, p=0.04) and had significantly higher rates of severe bleeding (6.3% vs 1.1%, p=0.04), vascular access site complications (8.4% vs 2.1%, p=0.04) and recurrent ischaemia at 30 days (7.4% vs. 2.1%, p=0.04). Major adverse cardiac events (MACE) were higher among young females, in comparison to young males (4.1% vs 2.1%, p=0.4). Young females experienced significantly higher rates of short-term net adverse clinical events (NACE) than young males (10.5% vs 3.2%, p=0.04). Female gender (odds ratio [OR] 11.7), diabetes (OR 2.5), hypertension (OR 1.78), decreased ejection fraction (OR 1.41) and smaller stent diameter (OR 1.15) were identified as independent predictors of adverse short-term outcomes among young ACS patients undergoing PCI. Conclusion: Young women experienced significantly more adverse short-term outcomes after PCI. They had significantly greater NACE, largely driven by increased rates of major bleeding. Female gender was an independent predictor of adverse short-term outcomes among young ACS patients undergoing PCI. Bangladesh Heart Journal 2018; 33(1) : 1-9